The Influence of Relativism and Universalism on the Formation of Ethical Standards - Khatuna Berishvili (Interdisciplinary Science Studies, 2025)
The cultural, social, and economic characteristics that exist in the world contribute to the diversity of ethical standards. Values and norms differ across the world's nations, leading to diverse ethical frameworks. In contemporary corporations, due to cultural diversity, making ethical decisions in an international business context is challenging. The integration of different cultures, legal systems, and social and economic conditions into universal ethical values is a complex task and one of the greatest challenges for modern corporations. The main ethical issue in international business is the conflict between cultural values and universal ethical norms, which defines ethical relativism. This issue is explored and analyzed in this article.